Does Body Mass Index of Nursing Students Correlate with Their Attitude towards Obesity? - Norwati, Daud; Salziyan, B; Ismail, SB (2018)
Health care personnel are important role models for promoting healthy lifestyle to general populations. Being overweight and obese are commonly associated with stigmas and discriminations. Stigma against obese people is common and it may relate to individual’s attitude on obesity. The study objective was to determine the correlation between body mass index of nursing students and their attitude towards obesity. A cross-sectional study was conducted between December 2011 and February 2012. Self-administered questionnaires were distributed to 297 nursing students in private colleges in Kelantan, Malaysia. Socio-demographic data, body mass index (BMI) and attitude towards obesity by using the ATOP score were obtained. Data was analyzed using SPSS version 20.0. Majority of the participants were Malays (99.7%), female (89.9%) and single (96.3%). About 64.3% had normal BMI, 18.9% underweight, 13.8% overweight, 2.4% obese type I and 0.7% obese type II. The ATOP score were ranging from 26.0 to 99.0 with mean (SD) of 62.8 (13.36). The attitude towards obese persons among the participants was more toward positive attitude. Body mass index (BMI) was skewed to the left distribution with the median (IQR) 20.8 (3.9). The correlation between attitude score and BMI was found to be not significant with p-value of 0.47 and Pearson correlation coefficient 0.04. Thus, there was no correlation between attitude towards obesity and individual’s BMI. Nursing students has positive attitude towards obesity. Their BMI does not seem to affect their attitude towards obese persons and reflects that there was no stigma towards obese person.